Buddhist Traditional Sangha of Russia in Socio-Cultural Processes Modern Buryatia - D. D. Amogolonova (Научный диалог, 2021)
Using the example of Buddhism in Buryatia, the article examines the problem of the post-Soviet return of religion from the periphery to the center of socio-cultural processes. It is noted that this means their secularization in the sense of the active participation of the clergy in a variety of secular practices, including the spheres of economics, politics and ideology. The author pays attention to the identification role of religion, based on the definition of Buddhism as the main cultural marker of the region, contributing to the formation of a territorial cultural text, the involvement in which is felt by all residents of the republic, regardless of the declared religiosity. Based on many years of research, the author analyzes the qualitative changes in the activities of the Buddhist traditional Sangha of Russia, aimed at protecting the Buryat culture and traditional economy, which makes it enter into both dialogue and confrontation with the secular authorities of the republic. It is shown that in the conditions of high secularization of social and individual consciousness, the Khambo Lama and other clergymen see their task in the spiritualization of everyday practices through the preservation of the social basis of Buddhism, represented by rural Buryats.